Treatment of Borderline Personality Disorder in Cognitive Behavioral Therapy: A Case Report - Berk İşlek; Meryem Karaaziz (Clinical Journal of Health Sciences, 2026)
Borderline Personality Disorder (BPD) is a personality structure characterized by significant instability in affect regulation, interpersonal relationships, and self-concept, leading to substantial impairment in functioning. This case report presents the Cognitive Behavioral Therapy (CBT) process applied to a 26-year-old female client for whom a clinical diagnosis of BPD was considered. Clinical interviews conducted in accordance with DSM-5 diagnostic criteria, together with findings obtained from the Minnesota Multiphasic Personality Inventory (MMPI), indicated a clinical profile marked by emotional instability, interpersonal sensitivity, impulsive behaviors, and chronic feelings of emptiness. The therapeutic process consisted of eight individual sessions conducted weekly, each lasting approximately 50 minutes. Interventions included psychoeducation, the ABC model, thought records, cognitive restructuring, behavioral activation, relaxation exercises, and role-playing techniques. The primary therapeutic goals were to enhance emotion regulation skills, reduce maladaptive and risky behavioral patterns, and improve interpersonal boundary-setting abilities. Clinical observations and client self-reports indicated improvements in emotional awareness, perceived self-control, and interpersonal functioning. This case study aims to contribute to the literature by demonstrating the applicability and clinical utility of cognitive behavioral therapy in individuals presenting with borderline personality features